Computing and combinatorics 14th Annual International Conference, COCOON 2008, Dalian, China, June 27-29, 2008 : proceedings - COCOON (Conferência) (Lecture notes in computer science ;)
The refereed proceedings of the 14th Annual International Computing and Combinatorics Conference, COCOON 2008, held in Dalian, China, in June 2008. The 66 revised full papers presented were carefully reviewed and selected from 172 submissions. The papers are organized in topical sections on algorithms and data structures, algorithmic game theory and online algorithms, automata, languages, logic, and computability, combinatorics related to algorithms and complexity, complexity theory, cryptography, reliability and security, and database theory, computational biology and bioinformatics, computational algebra, geometry, and number theory, graph drawing and information visualization, graph theory and algorithms, communication networks, and optimization, wireless network, network optimization, and scheduling problem.